Thickness and temperature dependence of magnetic anisotropies of Ni77Mn23 films - (:unkn) unknown (ELSEVIER SCIENCE BV, 2001)
Magnetic properties of polycrystalline reentrant Ni77Mn23 films of various thickness ( 50, 100, 300, 600, 1000 and 3700 Angstrom) were studied by both spin wave resonance (SWR) and DC magnetization techniques as a function of temperature. All films show spin-glass properties at the temperature range below freezing temperature T-f (congruent to 120 K). For temperatures well-above T-f, most of the films exhibit multi-peak ESR spectra at both X-and Q-band when the external field is oriented within a small interval of a solid angle around the film normal. The number of peaks increases with film thickness, indicating long spin wave excitation across the film thickness. The angular dependent SWR spectra were successfully analyzed by usual classical SWR theory. Hence, the SWR parameters were deduced for magnetic energy density including Zeeman, effective magneto-crystalline and unidirectional bulk and surface anisotropies, oblique anisotropy, spin-wave energy (exchange energy) and magnetic damping terms. The effective exchange stiffness parameter (D) remains practically the same for all films above T-f, while its value surprisingly increased below T-f, showing a strong correlation with spin-glass properties. The films also show easy-axis (perpendicular to the film plane) bulk and easy-plane surface anisotropy energies. The bulk anisotropy was found to strongly increase with decreasing temperature and film thickness, while linearly a temperature dependent surface anisotropy showed a very weak thickness dependence, This easy-plane surface anisotropy on both substrate and free surfaces has been attributed to an intrinsic property for NiMn films rather than accidental surface condition that could be varied from film to film due to variable sample preparation conditions. Furthermore, the spin disorder becomes more significant for thicker films. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: Ni77Mn23 films; magnetic anisotropy; SPIN-WAVE RESONANCE; NI-MN ALLOYS; FERROMAGNETIC-RESONANCE; SURFACE ANISOTROPY; AMORPHOUS FILMS; THIN-FILMS; GLASS; RESISTIVITY; BEHAVIOR; STATE